Shiga toxin-producing Escherichia coli plasmid diversity reveals virulence potential and control opportunities in animal hosts - Ali Nemati; Mahdi Askari Badouei; Gholamreza Hashemitabar; Maryam Hafiz (Scientific Reports)
Abstract Shiga toxin-producing Escherichia coli (STEC) is a significant public health concern, with plasmids playing a key role in its pathogenicity. This study investigates the relationship between plasmid types, virulence genes, and host specificity in 96 STEC strains isolated from cattle, sheep, goats, and pigeons in Iran. We examined the distribution of plasmid-encoded virulence genes, including astA, cma, cba, rhsA1, rhsA2, rhsC, stcE, katP, toxB, espP, subAB, ihaG, LAA iha, saa, etpD, cif, and epeA, along with ehxA subtypes and plasmid replicon types using PCR and RFLP analysis. The most frequently detected virulence factors, rhsC and ihaG, were associated with ehxA subtype A and IncFIB/IncK/B plasmids. Pigeon-derived isolates had a unique virulence profile, including cif but lacking ehxA, suggesting distinct pathogenic mechanisms. stcE and etpD were exclusive to positive controls O157 isolates, linked to ehxA subtype B and IncFIB plasmids. The predominance of ehxA subtype A in ruminants highlights potential host-specific associations. The widespread presence of IncFIB plasmids suggests their broad role in STEC pathogenicity. These findings highlight the critical role of plasmid-encoded virulence factors in STEC pathogenesis and underscore the need for targeted surveillance and control strategies tailored to specific host populations.